Effect of Heat–Moisture Treatment on Physicochemical, Thermal, Morphological, and Structural Properties of Mechanically Activated Large A‐ and Small B‐Wheat Starch Granules. Issue 10 (20th September 2019) - Hong, Jing; Li, Limin; Li, Chaopeng; Liu, Chong; Zheng, Xueling; Bian, Ke
Abstract : Abstract: The large and small granules of A‐starch (AS) and B‐starch (BS) were separated from wheat cultivar of ZM 22. It was modified by ball‐milling (BM) and heat–moisture treatment (HMT) was performed after BM treatment. After BM, noticeable deformation, fragments, fissures, and grooves were observed, whereas diffusion and aggregation were detected and followed by HMT. Crystallinity of AS‐BM‐5h decreased to 7.8%, and no diffraction peaks were observed for BS. However, after HMT, the crystallinity of AS‐BM‐5h and BS‐BM‐5h was increased to 17.4% and 6.2%, respectively. AS–BM–HMT displayed better thermal stability. After being treated by BM previously, AS and BS showed an increase in solubility, whereas the subsequent HMT of BM‐treated starches (both AS and BS) had higher solubility especially for BS with longer BM treatment time. Large‐sized granules were easier to be damaged by BM, whereas small‐sized granules were greatly influenced by HMT. Dual modification of BM–HMT was an effective and potential method to modify the structure of wheat starch granules and expand its industrial applications. Practical Application: This study put forward a new dual modification method in combination with BM–HMT for large A‐starch and small B‐starch granules. Flour processing inevitably causes some starch to be damaged by destroying the structure. How can the damaged starch structure be improved to satisfy the food processing industry? HMT was proposed to modify the mechanically activated starches because of its obvious effects on smaller BS. HMT can reduce the content of damaged starch by rearranging and reorganizing its structures. This study can provide a low‐cost, convenient, and eco‐friendly technology for improving damaged starch and developing its applications in food industry.